Analisis Faktor-Faktor yang Mempengaruhi Keputusan Berkunjung Wisatawan di Waterworld Lampung - Koimah; Supriyadi, Heri; Mardian, Husni (STIES ALIFA, 2023)
The tourism business is one of the most promising businesses to be built after the Covid-19 pandemic. In Lampung itself, many new tourism businesses have emerged that have just opened in 2022, precisely after the Covid pandemic ends. One of them is Waterworld Lampung. The only waterpark that presents an exotic instagrammable impression in Lampung, with ocean wave rides and rainbow slides. The research method used in this study is quantitative, with a total sample of 37 respondents, with a survey data collection method using a questionnaire. The analysis technique used is multiple linear regression with the regression equation Y = C + b1X1 + b2X2 + e with the dependent variable being Tourist Visiting Decisions (Y), and the independent variables are Sosial Media Advertising (X1) and Ticket Prices (X2). The results of the study stated that in a partial t-test that the probability values ​​​​of XI and X2 <0.5, meaning that there is a positive and significant influence partially between the independent variable and the dependent variable. Simultaneously f test, the probability of XI and X2 <0.5 means that there is a positive and significant influence partially between the independent variable and the dependent variable together. This means that the more Waterworld Lampung continuously advertises on sosial media and provides affordable ticket prices, the higher the interest of tourists to visit.